2021
DOI: 10.7717/peerj.10525
|View full text |Cite
|
Sign up to set email alerts
|

The natural product biosynthetic potential of Red Sea nudibranch microbiomes

Abstract: Background Antibiotic resistance is a growing problem that can be ameliorated by the discovery of novel drug candidates. Bacterial associates are often the source of pharmaceutically active natural products isolated from marine invertebrates, and thus, important targets for drug discovery. While the microbiomes of many marine organisms have been extensively studied, microbial communities from chemically-rich nudibranchs, marine invertebrates that often possess chemical defences, are relatively unknown. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
1
17
1
1
Order By: Relevance
“…The detection of many compounds with cytotoxic activity and antimicrobial activity suggests that Streptomyces strain 63 could contribute to the defense of C. quadricolor from fungi, bacterial infections, and predation. In our previous study of strain 63, the ethyl acetate extract of the liquid culture medium exhibited antimicrobial and antitumor activity, and genomic DNA was shown to harbor several biosynthetic gene clusters, including polyketide synthase (PKS; type I and type II) and non-ribosomal peptide synthetase (NRPS) gene clusters [ 58 ]. Our results reinforce the hypothesis that the nudibranch-associated microbiome is a significant source of bioactive compounds, which may support the nudibranch’s chemical defense.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of many compounds with cytotoxic activity and antimicrobial activity suggests that Streptomyces strain 63 could contribute to the defense of C. quadricolor from fungi, bacterial infections, and predation. In our previous study of strain 63, the ethyl acetate extract of the liquid culture medium exhibited antimicrobial and antitumor activity, and genomic DNA was shown to harbor several biosynthetic gene clusters, including polyketide synthase (PKS; type I and type II) and non-ribosomal peptide synthetase (NRPS) gene clusters [ 58 ]. Our results reinforce the hypothesis that the nudibranch-associated microbiome is a significant source of bioactive compounds, which may support the nudibranch’s chemical defense.…”
Section: Resultsmentioning
confidence: 99%
“…SCSIO 001680 was preserved as a lyophilized sample. It was cultivated as previously described [ 58 ]. Briefly, strain 63 was inoculated on an isolation medium R2A plate and incubated at 30 °C for five days.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the detection of polyketide synthase (PKS) and nonribosomal peptide synthetase (NRPS) genes in the association of nudibranchs with bacteria could further explain their essential role in chemical defense in the nudibranchs. The purification of these nudibranch-associated bacterial genes has been conducted (Riyanti et al, 2009;Böhringer et al, 2017;Kristiana et al, 2020;Abdelrahman et al, 2021). The most recent study by Abdelrahman et al (2021) reported that nudibranch-associated bacteria have antibacterial activity and possess natural product gene clusters.…”
Section: Revised Amendments From Versionmentioning
confidence: 99%
“…The purification of these nudibranch-associated bacterial genes has been conducted (Riyanti et al, 2009;Böhringer et al, 2017;Kristiana et al, 2020;Abdelrahman et al, 2021). The most recent study by Abdelrahman et al (2021) reported that nudibranch-associated bacteria have antibacterial activity and possess natural product gene clusters. In the present study, nudibranch-associated bacteria with potential bioactivity found in the Jepara coastal waters of the Java Sea were molecularly identified to determine their diversity, antimicrobial activity, and the presence of PKS and NRPS gene fragments.…”
Section: Revised Amendments From Versionmentioning
confidence: 99%
“…The quality of the extraction methods to access diversity in the microbiome associated with C. quadricolor was examined by 16S rRNA community analysis and nextgeneration sequencing, whereas bioinformatics analyses and ecological statistics were performed as described previously [16]. The V4 region of 16S rRNA was amplified to prepare Illumina MiSeq libraries using environmental DNA protocol generated by Kozich et al [17].…”
Section: S Rrna Community Analysis Of C Quadricolormentioning
confidence: 99%